Green Finance and Regional Technological Innovation in China: The Mediating Role of R&D Investment - Ading Li; Adul Supanut; Jianxu Liu (International Journal of Financial Studies)
In light of global initiatives aimed at promoting sustainability and low-carbon growth, this research investigates how green finance affects regional technological innovation in China, specifically highlighting the mediating effect of R&D investment. Utilizing panel data from 30 provinces in China from 2008 to 2021, we apply fixed-effects and mediation models to explore these relationships. The results indicate a strong positive link between green finance and regional technological innovation, with R&D investment acting as a partial mediator. Furthermore, the capabilities for regional innovation and entrepreneurship enhance the influence of green finance on R&D investment. However, in areas with greater innovation and entrepreneurship capabilities, the additional effect of R&D investment tends to decrease. Based on these results, the study proposes targeted policy recommendations, including enhancing green finance policies, improving financial institution services, promoting enterprise-led R&D activities, and fostering regional collaboration to achieve balanced innovation development. These insights provide both theoretical and practical significance for leveraging green finance to advance sustainable innovation.